Rationale and design of INFINITY-SWEDEHEART: A registry-based randomized clinical trial comparing clinical outcomes of the sirolimus-eluting DynamX bioadaptor to the zotarolimus-eluting Resolute Onyx stent - Erlinge, David; Andersson, Jonas; Fröbert, Ole; Törnerud, Mattias; Böhm, Felix; Held, Claes; Elek, Candace; Sirhan, Motasim; Oldgren, Jonas; James, Stefan (The American heart journal, 2024)
Modern drug-eluting stents have seen significant improvements, yet still create a rigid cage within the coronary artery. There is a 2% to 4% annual incidence of target lesion failure (TLF) beyond 1 year, and half of the patients experience angina after 5 years. The DynamX bioadaptor is a sirolimus-eluting, thin (71 µm) cobalt-chromium platform with helical strands that unlock and separate after in vivo degradation of the bioresorbable polymer coating. This allows the vessel to return to normal physiological function and motion, along with compensatory adaptive remodeling, which may reduce the need for reintervention and alleviate angina following percutaneous coronary intervention (PCI). The INFINITY-SWEDEHEART trial is a single-blind, registry-based randomized clinical trial (R-RCT) to evaluate the safety and effectiveness of the DynamX bioadaptor compared to the Resolute Onyx stent in the treatment of patients with ischemic heart disease with de novo native coronary artery lesions. The R-RCT framework allows for recruitment, randomization, and pragmatic data collection of baseline demographics, medications, and clinical outcomes using existing national clinical registries integrated with the trial database. The primary objective is to demonstrate noninferiority in terms of freedom from TLF (cardiovascular death, target vessel myocardial infarction, or ischemia-driven target lesion revascularization) at 1 year. Powered secondary endpoints will be tested sequentially for superiority from 6 months to the end of follow-up (5 years) for the following: 1) TLF in all subjects, 2) target vessel failure in all subjects, and 3) TLF in subjects with acute coronary syndrome (ACS). Subsequent superiority testing will be performed at a time determined depending on the number of events, ensuring sufficient statistical power. Change in angina-related symptoms, function and quality of life will be assessed using the Seattle Angina Questionnaire-short version. Predefined sub-groups will be analyzed. In total, 2400 patients have been randomized at 20 sites in Sweden. Available baseline characteristic reveal relatively old age (68 years) and a large proportion of ACS patients including 25% STEMI and 37% NSTEMI patients. The INFINITY-SWEDEHEART study is designed to evaluate the long-term safety and efficacy of the DynamX bioadaptor compared to the Resolute Onyx stent in a general PCI patient population. [Display omitted]